Sintesis Selulosa Asetat Dari Limbah Kertas HVS Dengan Variasi Temperature dan Waktu Hidrolisis - Hasriani, Dila; Adriana, Adriana; Zulkifli, Zulkifli (Jurnal Riset, Inovasi, Teknologi & Terapan, 2022)
Cellulose acetate can be made by utilizing raw materials that contain cellulose, one of which is waste paper. It has been reviewed that waste paper still contains high cellulose. The purpose of this study was to determine the effect of variations in temperature and reaction time on cellulose acetate products in the hydrolysis process. The method used in this research is cellulose activation, acetylation and hydrolysis with the steps taken include preparation of raw materials, delignification and purification of cellulose acetate. The synthesis of cellulose acetate was carried out by adding glacial acetic acid to the delignified paper, then adding acetic anhydride and sulfuric acid in the acetylation process to produce triacetate cellulose products, then the product was reacted with water to reduce the degree of substitution so that the resulting product was cellulose diacetate. The temperature variations used are 30, 40, 50 and 60 oC with time variations of 90, 120, 150, and 180 minutes. The product is then filtered and washed until neutral using distilled water. The resulting cellulose acetate was then analyzed for acetyl content, degree of substitution, and FTIR test. From the results of the research, the best acetyl levels and degrees of substitution were obtained at a temperature of 60 C and a time of 180 minutes, namely 39.46% and DS 2.42. The characteristics of cellulose acetate with FTIR of the functional group indicated the presence of cellulose acetate compounds with a sharp peak in the C = O ester group of the acetyl group with a wave number of 1622.13 cm-1 and the appearance of an O-H group from cellulose with a wave number of 3549 cm-1 and 3404. cm-1. Cellulose acetate produced from this research is a solid like white flour